(untitled) (Journal of Ideas in Health, 2023)
Background: Osteoporosis is known to cause long-acting disability. This study aimed to explore the knowledge, and preventive practice among women attending the primary health centers (PHC) in Al Ramadi City, west of Iraq. Methods: A cross-sectional study was conducted between January and March 2022. A simple random sampling technique was recruited to collect samples using face-to-face interviews of women during the routine visit to PHCs. Univariate and bivariate were used to analyze the data. The statistical package for the social sciences was used for data analysis. Results: Two hundred and fifty women were interviewed with a mean age of 37.9 ±11.3 years. The majority of them were married (87.0%), and unemployed or housewives (66.0%). Although, most of the participants heard about osteoporosis (238, 95.2%), and the possibility to cause pain before the occurrence of fracture (67.6%), the average knowledge score on osteoporosis was 55.75 ± 18.87. Furthermore, the surveyed women reported that practices of sunlight exposure (p=0.000), calcium-rich foods (p=0.003), and Vitamin D supplementation (p=0.022) are significantly related to reducing the risk of Osteoporosis. Healthcare providers played a significant role to support women with osteoporosis-related knowledge. Conclusion: Although most women heard about the disease, their level of knowledge was modest, which might affect the measures necessary to prevent the disease.